Enhanced Medical Image Watermarking Scheme with CLA-HE& DWT, SVD Transforms - Gajula, Srinivasarao; V, Rajesh (International Journal of Engineering and Technology, 2018)
In order to get clear information regarding patient it is necessary to enhance medical images like MRI, CT scan, ultrasound etc.Â  For clinical diagnosis, we have to transmit it through the communication network. During this process information must be protected from malicious users. In this process these images are manipulated, so to protect these images we have to follow some security requirements. In this paper, we are increasing the quality of the image by using enhancement with clahe technique and that enhanced image is watermarked for security purpose by using DWT, SVD transforms with a scaling factor as uniform distribution function. The performance evaluation parameters will give better results for medical as well as under water images. The obtained results are very helpful for integrity of medical images. The technique will provide better response for medical images. This method will give good results in terms of improvement in output, Peak Signal to Noise Ratio (PSNR) and Mean Square Error (MSE).Â Â